Effects of ternary mixed crystal and size on intersubband optical absorption in wurtzite InGaN/GaN core–shell nanowires. (July 2015) - Liu, W.H.; Yang, S.; Feng, H.M.; Yang, L.; Qu, Y.; Ban, S.L.
Highlights: We calculated optical absorptions in CSNWs with finite wide barrier and finite high potential. The TMC and size effect on optical absorptions in CNSWs are investigated. Saturation phenomenon of optical absorptions in CNSWs are also discussed. Abstract: Based on the density matrix approach, the effects of ternary mixed crystal and size on intersubband optical absorption coefficients in Inx Ga1− x N/GaN core–shell nanowires (CSNWs) are investigated. The results show that the optical absorption can be modulated by In component x and the size of CSNWs, since the variation of electron states in these systems. It is found that photonic frequencies of resonant absorption and the absorption coefficient increase obviously when x increases or the radius of InGaN core reduces, while the half-width of the coefficient decreases as its peak becomes higher and sharper. A saturation phenomenon of optical absorption is also found when the incident light intensity exceeds a certain value. The theoretical results are expected to be helpful to develop CSNW optic devices.